Harga, Pelayanan, dan Promosi Terhadap Keputusan Pembelian Pelanggan - Cherish Cherish; Angelly Pratiwi; Hasiholan P. Manik; Billy Gunawan; Rosinta Romauli Situmeang; Firmansyah Firmansyah (IPM2KPE, 2023)
This study aims to determine the effect of price, service, and promotion on customer purchasing decisions at PT. Tirtasari Pure Source. This research method is Quantitative. The population of this research is 118 customers. Data will be analyzed by validity test, classical assumption test, and hypothesis test. The results showed that price has a negative and significant influence on purchasing decisions. Service has a positive and significant influence on Purchasing Decisions. Promotion has a positive and significant influence on Purchase Decision. Simultaneously Price, Service and Promotion have a significant influence on Purchasing Decisions. Keywords: Price, Purchase Decision, Service, Promotion